(untitled) (Mustansiria Dental Journal, 2018)
The successful outcome of endodontic treatment depends on the reduction or elimination of bacteria present in an endodontic infection. It has been reported that chemo-mechanical instrumentation alone is not enough for this purpose. The purpose of this in vitro study was to compare the pH changes that occurred over a period of 14 days using four types of calcium hydroxide. Four types of calcium hydroxide materials were filled in fifty extracted single rooted teeth which were kept in individual vials containing distilled water at a pH of (7.4). Digital pH-meter was used to measure the pH of different groups at two hours, 24 hours, 7 days & 14 days after immersion of the specimens. The mean pH was found for all groups and statistical analysis was carried out using ANOVA and POST HOC TEST (LSD). Calcium hydroxide was found to significantly raise the root PH. Therefore calcium hydroxide is an effective choice in clinical practice to be used as intra canal medicament between appointments.